The Characteristics of Teaching Materials that Promote Mathematical Abstraction through the Visualization of Minangkabau Batik Motifs - Afriyani, Dona; Ramadhani, Lailatul; Yenti, Isra Nurmai; Herlina, Elda (Mathematics Education Journal, 2024)
The ineffective use of constructivist learning through mathematical abstraction activities by teachers has led to low mathematics learning results. To promote mathematical abstraction, teaching materials must integrate the visualization of Minangkabau batik motifs. Therefore, this research aimed to describe the characteristics of teaching materials by adopting a 4D developmental model. The data analysis across the development stage included qualitative descriptive analysis for data received from interviews, observations, document reviews, and literature reviews, as well as quantitative descriptive analysis for data obtained from wide validation. The results showed that (1) Minangkabau batik motifs contained the concept of transformation geometry including reflection, rotation, translation, and dilation. (2) The characteristics of teaching materials included (a) having a cover, encouragement sheet, foreword, table of contents, materials, supporting information, exercises, assessments, and bibliography, (b) meeting the appropriateness of graphics, content, and language, (c) displaying the visualization of Minangkabau batik motifs for presentation of material, exploration of the properties of transformation geometry, and finding answers to prompting and practice questions, as well as (d) containing student activities in constructing concepts and making connections between such concepts. In conclusion, this research could help teachers improve students' mathematical abstraction using local cultures and teaching materials.